Secondary Epileptogenesis: Common to See, but Possible to Treat? - Shen, Yujia; Gong, Yiwei; Ruan, Yeping; Chen, Zhong; Xu, Cenglin (Frontiers in Neurology, 2021)
Secondary epileptogenesis is a common phenomenon in clinical epilepsy, in which epileptiform discharges occasionally originate from the regions outside the primary focus. It is one of the major causes for pharmacoresistance and surgical failure. Compared with primary epileptogenesis, the mechanism of secondary epileptogenesis is usually more complex and diversiform, which is still not fully illuminated. In this review, we aim to summarize findings of the characteristics of both clinical and laboratory secondary epileptogenesis in a historical view. Further, we discuss the possible mechanisms of secondary epileptogenesis in molecular, cellular and circuity levels. Meanwhile, the potential treatments for secondary epileptogenesis including pharmacotherapy and neuromodulation are presented. At last, we prospect those future experimental designs should take into account the circuitry view as stepping stones for the precise treatment of secondary epileptogenesis in the future.